(untitled) (Universal International Scientific Journal, 2026)
This article analyzes the issues of developing critical thinking competence in the educational process from a theoretical and practical perspective. In the modern education system, the formation of an individual’s independent, analytical and reflective thinking skills is recognized as an important condition for improving the quality of education. The article highlights the essence of critical thinking competence, its pedagogical significance and ways of its effective development in the educational process based on scientific sources.